The Phenomenon of Flypaper Effect In Regencies/Municipality in Lampung Province - Sudrajat Sudrajat (Politeknik Negeri Lampung, 2010)
The main objective of this research is to provide empirical proof of occurrence the influence of DAU and PAD on local expenditure in regencies/municipality in Lampung. The other objective is to examine existence of different flypaper effect, a condition when regencies/municipality give different respon in determining local expenditure based on centreal goverment transfer compared winth local revenue.This research is using multiple regression model for analyzing sample data from 10 regencies/municipality. Analyzed data is time series that consist of PAD, DAU and BD which taken from local budget and revenue report for ten years from 1998 until 2007.Result of analysis indicates that DAU influence toward BD in more significant than the influenced PAD toward BD which mean taht flypaper effect occur in all regencies/municipalities of Lampung. This situation gives the evidence taht local goverment just wait the amount of DAU received before deciding the amount of expenditure (Sukriy & Halim, 2003), so that the upcoming period of expenditure will be greater. The result of this research is merely based on statistical analysis and canâ€™t be used as sole measurement of regencies/municipalities of Lampung performance. The result still require confirmation through future researches.Â Keywords : DAU, PAD, regional budget report, flypaper effect.